Estimativa do Consumo Voluntário do Capim-Tanzânia (Panicum maximum, Jacq. cv. Tanzânia) por Vacas em Lactação sob Pastejo Rotacionado - Pereira Lima, Maria Lúcia [UNESP]; Berchielli, Telma Teresinha [UNESP]; Nogueira, José Ramos; Ruggieri, Ana Cláudia; Magalhães Aroeira, Luiz Januário; Dias Salman, Ana Karina [UNESP]; Guimarães Soares, João Paulo [UNESP] (My University, 2001)
The trial was carried out in a Tanzania grass (Panicum maximum) pasture, rotationally grazed by lactating cows, to estimate the dry matter intake. Three treatments were tested: crossbred cows fed 3 kg per day of concentrate and crossbred and Zebu cows (Gyr) without concentrate supplementation. The forage availability was 7,340.2 kg of dry matter (DM) /ha before and 5,639.5 after the 3rd grazing day. The Tanzania grass DM intake was 8.26 ± 5.66, 11.01 ± 5.37 and 9.55 ± 2.31 kg of DM/cow/day per day or 2.15, 2.37 and 2.34% of live weight, respectively, for the supplemented crossbred cows and non supplemented crossbred and Zebu cows. The average milk production was higher for the supplemented group (11.98 kg/cow/day). The milk production observed by the non supplemented cows was similar. Milk yield of 6.53 was obtained for non supplemented crossbred cows and 5.46 kg per cow/day was performed for the Zebu cows.
Estimation of Voluntary Intake of Tanzania Grass (Panicum maximum, Jacq. cv. Tanzânia) Rotationally Grazed by Lactating Cows
Keywords: Crossbred cows; Dry matter intake; Gyr cattle; Tropical pasture